Technology Innovation Capability and Its Effect on Corporate Financial Accountability in South Africa - Rajesh Naidoo (Journal of Business Innovation and Accounting Research, 2024)
This study investigates the relationship between technology innovation capability and corporate financial accountability within the South African business context. As organizations increasingly adopt technological innovations to enhance their operational efficiency and financial management practices, understanding the mechanisms through which technology innovation capability influences financial accountability becomes paramount. Employing a quantitative research methodology utilizing Structural Equation Modeling with Partial Least Squares (SEM-PLS) analysis through SmartPLS software, this research examines how technological capabilities—including accounting information systems, digital financial tools, and information technology utilization—affect the quality of financial reporting and accountability mechanisms in corporate entities. The findings reveal that technology innovation capability significantly and positively influences corporate financial accountability through enhanced financial reporting quality, improved transparency mechanisms, and strengthened internal control systems. Furthermore, the study identifies that human resource competence and organizational factors serve as critical moderating variables in this relationship. The implications of these findings extend to policymakers, corporate managers, and regulatory bodies seeking to enhance financial accountability through strategic technology adoption. This research contributes to the existing body of knowledge by providing empirical evidence from the South African context, thereby addressing a significant gap in the literature concerning technology-driven financial accountability in emerging economies.